An integrated model of the water transport in nonuniform compressed gas diffusion layers for PEMFC. (21st May 2019) - Xu, Yifan; Qiu, Diankai; Yi, Peiyun; Lan, Shuhuai; Peng, Linfa
Abstract: Water transport in gas diffusion layer (GDL) is a very important issue for high power density Proton Exchange Membrane Fuel Cell (PEMFC). During the GDL and bipolar plate (BPP) assembly process, the water transport behavior is greatly influenced by the nonuniform compression on the GDL, which leads to uneven distribution of the internal mass transport pores. In this study, an integrated model is developed to predict the water transport in nonuniform compressed GDL. Firstly, a GDL compression deformation model is built to obtain the relationship between the GDL deformation and assembly clamping force based on energy method. Then, a water transport model is established by considering the probability density function (PDF) of the pore size for the compressed GDL. The accuracy of the integrated model has been verified by comparing with the finite element method (FEM) and the computational fluid dynamics (CFD) simulation results. The influence of assembly clamping force, GDL thickness and channel geometry are analyzed based on the integrated model. Drainage pressure increases monotonically with the assembly clamping force and is divided into three stages. For the baseline case, 0.2 mm of GDL thickness and small rib-channel ratio is conducive to improving drainage capacity. It provides the guidance for matching of GDL/BPP assembly condition and performance prediction of PEMFC. Highlights: Nonuniform compression induces different water transport from the uncompressed GDL. An integrated model is developed to predict the water transport. The probability density function (PDF) of the pore size is considered. Evaluated the influence of assembly force, GDL thickness and the channel geometry. Rapidly applied in flow field design and GDL assembly matching.